(untitled) (Research, Society and Development, 2022)
Objective: To identify information concerning nursing care in the treatment of pressure injuries with low-level laser; To prototype a software with information about nursing care in the treatment of pressure injuries with low-level laser to support professional clinical decision-making. Methodology: Qualitative research, of the methodological study type, through Prototyping. The Operationalization method was used, through cyclic prototyping, carried out through four stages, in the present study developed until the third stage, leaving the fourth stage for future studies. Results: They were divided into the 3 methodological stages in which the study was developed. 1, communication, there was a discussion about the use of low-level laser by nurses in the treatment of wounds, then the existence of technologies with information to treat pressure injuries with laser therapy was observed and mapped. 2, rapid planning, operating system usage was defined, budget planning, graphic scheme, and written content definition. 3, construction of the prototype itself with all the screens proposed in the graphic scheme, budget planning, graphic scheme, and definition of the written content. Conclusion: It is concluded, therefore, that the objectives of the study were covered, and that there is a need to develop more studies like this one, in order to reaffirm the importance of technology and health education, which will have direct effects on care , in teaching and research.